ANIMAL FARM - Orwell, George, 1903-1950.; Bullard, Nick; Linley, Adam; Pitts, Sorrel (London : PENGUIN BOOKS, 2020)
Penguin Readers is an ELT graded reader series for learners of English as a foreign language. With carefully adapted text, new illustrations and language learning exercises, the print edition also includes instructions to access supporting material online.
Includes questions and excercises
Keywords: Readers; Animal stories -- Juvenile fiction; Readers